The relationship between perfectionism, cognitive flexibility and suicide ideation among Malaysian undergraduates - Chng, Zoe Woon Chin; Liew, Kee Yee; Tiong, Wei Jie (2022)
The rising of suicide at an alarming rate globally urges the recognition of suicide ideation, which refers to one’s desire and interest in suicide. Yet, the role of both perfectionism and cognitive flexibility in suicide ideation remains controversial and unclear to date. Thus, this study was designed to examine the predictive relationship between perfectionism, cognitive flexibility and suicide ideation among Malaysian undergraduates. A quantitative cross-sectional research design was used with three instruments including Frost Multidimensional Perfectionism Scale-Brief (FMPS-B), Cognitive Flexibility Inventory (CFI) and Scale for Suicidal Ideation (SSI), to assess the corresponding variables. The purposive sampling method was employed with specific inclusion criteria to recruit 18 to 25 years old Malaysian undergraduates. A total number of 262 Malaysian undergraduates (M = 22.18, SD =1.256) with 53.8% females (n = 142) were recruited through online self-reported survey. The results showed that perfectionism positively predicted suicide ideation, in contrast, cognitive flexibility negatively predicted suicide ideation. The present findings provided new insight into the existing literature regarding suicide ideation in the Malaysian context, and the empirical evidence that could serve as a reference for practitioners to sketch effective evidence-based interventions regarding suicide-related issues. Several limitations and recommendations of the study were discussed.